Lithium-Ion Supercapacitor Using Vertically-aligned Carbon Nanotubes from Direct Growth Technique, and its Electrochemical Characteristics - Azam,Mohd Asyadi (2019)
This paper reports the fabrication of a lithium ion supercapacitor from vertically-aligned carbon nanotubes (VACNTs) directly grown on a conductive substrate (SUS 310S alloy), using alcohol catalytic chemical vapour deposition technique. CNTs direct growth technique on an electrically conducting foil simplifies the electrode assembly, thus reducing the fabrication process, because the foil can directly act as a current collector. With the VACNT direct growth technique, the supercapacitor electrode was easily prepared and assembled with a non-aqueous 1 M LiPF6 electrolyte. Experimental results show that CNTs (multi-walled type structures of good quality) were perpendicularly grown to the substrate. This device demonstrates a specific capacitance of up to 101 F g-1 (at a scan rate of 1 mVs-1), and a high-rate capability, up to a scan rate of 1000 mVs-1. The VACNT electrode electrochemical performance was also measured by galvanostatic charge-discharge and electrochemical impedance spectroscopy. The effect of free standing CNTs direct growth on the current collector makes insulating binder material unnecessary, thus producing better ion accessibilities to its surface. This also contributes to the good and reliable electrochemical supercapacitor performance.